Whole corn rations for finishing heifers: A comparison of self-fed and mixed supplement, with and without salt. - Harbers, L.H.; Harrison, K.F.; Richardson, D.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
Twenty-four Hereford x Angus heifers averaging 714 lbs. were allotted by weight to four groups of six animals each to study effects on gain, feed intake, and feed efficiency of: 1. Free-choice whole corn without roughage. 2. Protein supplement either mixed with whole corn or supplied seperately (free-choice). 3. Omitting salt
Keywords: Beef; Corn; Finishing heifers; Salt